#### Answer

$f(2m-3)=-6m+13$

#### Work Step by Step

To find the value of $f(2m-3)$, substitute $2m-3$ to $x$ in $f(x)$ to obtain:
$f(x)=-3x+4
\\f(2m-3)=-3(2m-3)+4
\\f(2m-3) = -3(2m) +(-3)(-3)+4
\\f(2m-3)=-6m+9+4
\\f(2m-3)=-6m+13$

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

$f(2m-3)=-6m+13$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.